SOSIALISASI PEMANFAATAN SAMPAH SEBAGAI MEDIA PEMBELAJARAN IPA DI MI BUSTANUL ULUM KECAMATAN KALIWATES KABUPATEN JEMBER - Crismono, Prima (LPPM Universitas Insan Pembangunan, 2025)
Research on plastic waste aims to apply an environmentally conscious attitude to the students of Madrasah Ibtidaiyah Bustanul Ulum, regarding the reuse of plastic waste by creating a shadow that is more useful and suitable to use, of course, within the scope of learning. Our main goal is to reduce the risk of plastic waste accumulation, because this plastic waste is very difficult to decompose so it takes a very long time around 50-80 years to decompose naturally with the soil. The item that we will make is in the form of Solar System Learning Media from the plastic waste earlier. In the implementation of this activity, we use practicum observation methods and documentation. We fill in the observation method here by directly reviewing the research location and making power points related to educational materials during socialization for the creation of Learning Media, including preparing materials, tools, and auxiliary materials during the practicum later.